Didactic conditions of development of creative activity in art-graphic activity of students - Serdoletskaya, T.M. (Pedagogy of Higher and Secondary Education, 2006)
The didactic conditions of students creativity activation m the process of artisticand-graphical training of future fine arts teachers an examined.